Improving the Ability to Dance Mokarawo Gorontalo Creative Dance Using Audiovisual Media in 4th Grade Students of SDN 1 Batudaa - Pasue, Miftania; Pulukadang, Wiwy Triyanty; Pulukadang, Mimy Astuty; Karlan, La Ode; Husain, Rustam I (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study addresses the research question: